Solar availability for winter space heating: an analysis of the calendar period 1953-1975 - Asbury, J.G.; Maslowski, C.; Mueller, R.O. (Argonne National Laboratory, 1979)
Solar availability for space heating has been determined from an analysis of SOLMET data tapes for eight US sites. The tapes contain hourly readings of insolation and ambient temperature for the period 1953-1975. Scatter-diagrams of insolation versus heating degree-days, compiled on a daily basis, indicate a wide variation in insolation levels, even during periods of coldest weather. For seven of the eight sites, the peak-day backup energy required by a solar space heating system exceeded 85% of the peak-day energy requirement of a conventional (nonsolar) heating system.